Development of a combined photodynamic and sonodynamic therapy for the treatment of bacterial infections - Alagha, Heba. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2023., 2023)
Antimicrobial resistance is one of the biggest threats to global health. Developing new treatment modalities that can eradicate pathogens without inducing drug resistant strains, is of great necessity. Photodynamic therapy (PDT) is such a promising modality that aims to destroy pathogens using light-activated drugs, but is limited by the light penetration depth in tissues. Its close relative, sonodynamic therapy (SDT), has the capability to overcome this limitation, due to the superior tissue penetration of low-intensity ultrasound compared to light, but the full potential of this therapy has not been realized yet. The aim of this PhD research was to develop an e cient antimicrobial therapy via the combination of PDT and SDT. For this purpose, IR780 iodide loaded mesoporous silica nanoparticles were synthesized, and their antimicrobial photodynamic and sonodynamic potentials against gram-positive Staphylococcus au- reus and methicillin resistant Staphylococcus aureus, and gram-negative Pseudomonas aeruginosa and multi drug resistant Pseudomonas aeruginosa, were investigated. The antimicrobial photodynamic and sonodynamic potentials of free IR780 iodide were also investigated. The outcomes of the conducted studies demonstrated that both IR780 iodide and IR780 iodide loaded mesoporous silica nanoparticles can be utilized as photo/sono therapeutic agents, for the e ective inactivation of drug resistance bacteria. However, IR780 iodide loaded mesoporous silica nanoparticles are more suitable for clinical application. NOTE Keywords : Photodynamic therapy, Sonodynamic therapy, Antimicrobial resistance, IR780 iodide, Mesoporous silica nanoparticles, methicillin resistant Staphylococcus au- reus, multi drug resistant Pseudomonas aeruginosa.
Keywords: Photochemotherapy.; Anti-infective agents.; Bacterial diseases.